Preparation method of flexible solid electrolyte and preparation method of solid-state battery

Through the synergistic effect of COF materials with lithium salts and hydrophilic substances, a flexible solid electrolyte with high conductivity is prepared, which solves the volatility and cost of the electrolyte of traditional lithium battery, and realizes the stability and safety of lithium batteries, and reduces the stability and safety of lithium batteries. production costs.

CN119181871APending Publication Date: 2024-12-24SHANXI TAIHANG XINTONG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411309823.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The electrolytes in traditional liquid lithium-ion batteries are volatile and unsafe. The large amount of lithium salts required for aqueous lithium electrolytes leads to high cost and cannot meet the application requirements of lithium batteries.

Method used

Flexible solid electrolytes are prepared by using COF materials. By activating the synergy between COF and lithium salt and hydrophilic substances, a flexible solid electrolyte with high conductivity is formed. Combined with porous matrix and oven treatment, stable and safe lithium-ion battery electrolyte is prepared.

Benefits of technology

It realizes a flexible solid electrolyte with high conductivity at room temperature, ensures the charging and discharging stability and safety of the battery, reduces production costs, and meets the application needs of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181871A_ABST
    Figure CN119181871A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a flexible solid electrolyte and a preparation method of a solid-state battery. The preparation method comprises the following steps: step 1, activating COF; step 2, weighing PE and the activated COF, fully and uniformly grinding, adding liquid paraffin, fully and uniformly mixing, heating after uniformly mixing, after the PE is completely melted, putting the mixture on a roller press, rolling to form a flexible porous matrix, soaking the flexible porous matrix into dichloromethane, removing the liquid paraffin, and drying the flexible porous matrix in a drying oven to obtain a flexible porous material; a COF flexible porous matrix is obtained; step 3, taking a COF flexible porous matrix, weighing lithium salt and tetrahydrofuran, fully stirring, and removing the solvent in vacuum to obtain a flexible solid electrolyte precursor; and 4, quantitatively adsorbing hydrophilic substance steam by using the flexible solid electrolyte precursor prepared in the step 3 to obtain the COF flexible solid electrolyte. The method is simple in preparation process and low in cost; and the obtained Urea-COF solid electrolyte is stable in property and non-volatile, so that the safety and the stability are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and specifically relates to a method for preparing a flexible solid electrolyte and a method for preparing a solid-state battery. Background Art

[0002] With the development of the world, a large amount of natural energy has been developed and utilized by people, which has led to an energy crisis in the world. Therefore, the research on new energy sources is of great significance. As a new generation of clean energy, lithium batteries can not only avoid environmental pollution, but also facilitate people's lives and work.

[0003] As the market demand for electric vehicles continues to grow, lithium-ion batteries with high energy and power density have received great attention from business and research. Traditional electrolytes in liquid batteries are usually volatile and unsafe, which cannot meet their application requirements. Traditional aqueous lithium-ion battery electrolytes require high salt concentrations, and require a lot of lithium salts, which are expensive. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a flexible solid-state electrolyte and a method for preparing a solid-state battery, which solves the technical problems that traditional electrolytes in liquid batteries are usually volatile and unsafe, and that aqueous lithium-ion electrolytes require a large amount of salt, resulting in high costs.

[0005] In order to solve the above problems, the technical solution of the present invention is: a method for preparing a flexible solid electrolyte, comprising the following steps:

[0006] Step 1, activating COF;

[0007] Step 2, weigh PE and activated COF, grind them evenly, add liquid paraffin and mix them evenly, heat them after mixing, and after PE is completely melted, place the mixture on a roller press to roll it into a flexible porous matrix, soak the flexible porous matrix in dichloromethane, remove the liquid paraffin, and then dry the flexible porous matrix in an oven to obtain a COF flexible porous matrix;

[0008] Step 3, take the COF flexible porous matrix, weigh the lithium salt and tetrahydrofuran, stir them thoroughly, remove the solvent under vacuum, and obtain a flexible solid electrolyte precursor;

[0009] Step 4: quantitatively adsorb the hydrophilic substance vapor on the flexible solid electrolyte precursor prepared in step 3 to obtain a COF flexible solid electrolyte; wherein the COF flexible porous matrix is ​​Umg, the lithium salt is Vmg, the hydrophilic substance content is Xmg, and U:V:X=20~30:40~60:5~15.

[0010] Optionally, in step 2, the temperature is raised to 140-160° C. after mixing.

[0011] Optionally, in step 2, the flexible porous substrate is dried in an oven and then cut into circular shapes using a cutting machine.

[0012] Optionally, the hydrophilic substance is a substance containing hydrogen bonds.

[0013] Optionally, the hydrophilic substance vapor is water, water vapor, alcohol vapor or ammonia vapor.

[0014] Optionally, the COF material is a hydrophilic COF.

[0015] Optionally, the COF material is a COFs structure connected by urea groups.

[0016] Optionally, the COF material is Urea-COF.

[0017] Optionally, the lithium salt is LiTFSI, LiPF6 or LiBOB.

[0018] Optionally, in step 2, PE is Smg, COF is Rmg, liquid paraffin is Tmg, and R:S:T=9:1:1.

[0019] Optionally, in step 3, the ratio U:V:X=25:51.3:10.

[0020] Optionally, in step 3, the ratio U:V:X=25:51:10.

[0021] Optionally, in step 2, the rolling temperature of the roller press is 90°C.

[0022] Optionally, in step 3, the diffusion method is used, and the stirring time is 4 hours at room temperature; the time for removing the solvent anhydrous tetrahydrofuran under vacuum is 3 hours at 70°C; when quantitatively adsorbing hydrophilic substances, the temperature is raised to 100°C and maintained for 3 hours and then placed at room temperature for 20 minutes, and the temperature is repeatedly raised and lowered three times to quantitatively adsorb the hydrophilic substances.

[0023] Optionally, the method for preparing Urea-COF in the present invention comprises the following steps:

[0024] The two monomers trialdehyde pyrogallol and 1,1'-(1,4-phenylene) diurea were weighed into an ampoule tube according to a proportion, and solvents NMP, O-DCB and acetic acid solution were added; liquid nitrogen freeze-thaw cycle degassing, the ampoule tube was sealed, and then placed in a constant temperature oven at 80℃ to 90℃ for reaction for 70h to 75h; a yellow Urea covalent organic framework material, Urea-COF, was obtained;

[0025] The monomer trialdehyde phloroglucinol is Mmmol, 1,1'-(1,4-phenylene) diurea is Nmmol, the solvent NMP is OmL, O-DCB is PmL, and the acetic acid solution is QmL.

[0026] M:N:O:P:Q=0.05~0.2:0.075~0.3:0.6~1:0.1~0.3:0.05~0.2.

[0027] Optionally, M:N:O:P:Q=0.1:0.15:0.8:0.2:0.1.

[0028] Optionally, the concentration of the acetic acid solution is 6 mol / L.

[0029] Preferably, the reaction is carried out in a constant temperature oven at 90° C. for 72 hours.

[0030] Another object of the present invention is to provide a method for preparing a solid-state battery, which comprises coating the battery with a ratio of active material: binder: conductive agent = 7-9: 1-2: 1-2, drying the battery in a vacuum oven at 100-140°C and cutting the battery to obtain an LTO / LMO electrode sheet, and then assembling the prepared flexible solid electrolyte and electrode sheet in a button battery to obtain a full battery.

[0031] Optionally, the mass ratio of the pole piece is active material: binder: conductive agent = 8:1:1.

[0032] Optionally, the drying temperature of the electrode is 120° C. and the drying time is 6 hours.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention belongs to the field of solid electrolytes and aqueous lithium batteries. The COF flexible solid electrolyte provided by the present invention can suppress the anode hydrogen evolution caused by the hydrophilic substance through the hydrogen bonding of the urea group to the hydrophilic substance and the synergistic effect between the loaded lithium salt and the hydrophilic substance. The trace amount of hydrophilic substance acts as a carrier, greatly promoting the conductivity, thereby providing feasibility for the lithium battery to act as an electrolyte. The conductivity of the flexible solid electrolyte prepared by the present invention can reach σ=8.94×10-4S·cm at room temperature -1 , and meet the normal charging and discharging requirements of LMO / LTO.

[0035] The flexible solid electrolyte prepared by the preparation method of the present invention has excellent ionic conductivity while ensuring that water is not electrolyzed. The method has a simple preparation process, is easy to mass produce, has low assembly requirements, and is low in cost; the COF solid electrolyte obtained by the preparation method of the present invention is stable and non-volatile, which maximizes safety and stability, and can maintain stable cyclic charging and discharging during the battery charging and discharging process. The covalent organic framework material used in the present invention has a large specific surface area, a regular structure, a high porosity, and strong designability. The present invention utilizes the pore effect of COF and the structure on the COF pore wall to complete the restriction of water, ensure the conductivity value, and prepare a flexible water-based solid-state lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The process roadmap for preparing Urea-COF in Example 1;

[0037] Figure 2 is the X-ray powder diffraction pattern of Urea-COF prepared in Example 1;

[0038] Figure 3 The COF flexible solid electrolyte prepared in Example 1;

[0039] Figure 4 is the conductivity value of the COF flexible solid electrolyte prepared in Example 1;

[0040] Figure 5 is the charge and discharge curve of the solid-state battery in Example 3;

[0041] Figure 6 This is the cycle performance of the solid-state battery in Example 3. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0043] Example 1: Figure 3 and Figure 4 As shown, this embodiment provides a method for preparing a flexible solid electrolyte, comprising the following steps:

[0044] Step 1: activating Urea-COF to obtain activated Urea-COF;

[0045] Step 2: Weigh PE and activated Urea-COF and grind them evenly, add liquid paraffin and mix them well, heat them to 140-160°C after mixing, and after PE is completely melted, place the mixture on a roller press to roll it into a flexible porous matrix with a thickness of 18 μm, soak the flexible porous matrix in dichloromethane for 12 hours, remove the liquid paraffin, and then place the flexible porous matrix in an oven at 60°C for 1 hour to dry, remove the dichloromethane, and finally cut it into 9 mm round flexible porous matrices with a cutting machine, which is the same size as the CR20~ series diaphragms, to obtain a Urea-COF flexible porous matrix of about 10-14 mg;

[0046] Step 3: Take the Urea-COF flexible porous matrix, weigh the lithium salt and tetrahydrofuran, stir them thoroughly, and remove the solvent under vacuum to obtain a flexible solid electrolyte precursor;

[0047] Step 4: quantitatively adsorb the hydrophilic substance vapor on the flexible solid electrolyte precursor prepared in step 3 to obtain the Urea-COF flexible solid electrolyte; wherein the Urea-COF flexible porous matrix is ​​Umg, the lithium salt is Vmg, the content of the hydrophilic substance is Xmg, and U:V:X=25:51.3:10.

[0048] Through step 3, the Urea-COF flexible porous matrix and the lithium salt solution of tetrahydrofuran are mixed, and after the lithium salt is loaded, the temperature is increased and the solution is evacuated in a vacuum pump to obtain the Urea-COF flexible porous matrix loaded with lithium salt; the Urea-COF flexible porous matrix loaded with lithium salt is placed in a sealed glass container, and the hydrophilic substance vapor is quantitatively adsorbed to finally obtain the desired Urea-COF solid electrolyte.

[0049] In the method for preparing a flexible solid electrolyte of this embodiment, the hydrophilic substance is a substance containing hydrogen bonds. Optionally, the hydrophilic substance vapor is water, water vapor, alcohol vapor or ammonia vapor.

[0050] In the preparation method of a flexible solid electrolyte of this embodiment, the lithium salt is LiTFSI, LiPF6 or LiBOB.

[0051] In the preparation method of a flexible solid electrolyte of this embodiment, PE is Smg, Urea-COF is Rmg, liquid paraffin is Tmg, and R:S:T=9:1:1.

[0052] In the method for preparing a flexible solid electrolyte of this embodiment, the rolling temperature of the roller press is 90° C., and the roller press is performed five times to achieve the target thickness.

[0053] In the preparation method of a flexible solid electrolyte of this embodiment, the diffusion method is used in step 3, and the stirring time is 4 hours at room temperature; the time for removing the solvent anhydrous tetrahydrofuran under vacuum is 3 hours at 70° C. Then, the prepared Urea-COF flexible porous matrix is ​​placed in a closed container.

[0054] In the preparation method of a flexible solid electrolyte of the present embodiment, when quantitatively adsorbing hydrophilic substances, the temperature is raised to 100° C. and maintained for 3 hours each time, and then placed at room temperature for 20 minutes. The temperature is repeatedly raised and lowered for quantitative adsorption of hydrophilic substances three times to obtain Urea-COF solid electrolyte.

[0055]

[0056] It can be seen from the above table that U:V:S=25:51.3:10 has the best specific capacity and the highest battery capacity, so this ratio is preferred.

[0057] from Figure 4 It can be seen that the solid electrolyte prepared in this embodiment has good ion conductivity. Figure 4 The horizontal axis is the resistance, and the vertical axis is the derivative of the resistance.

[0058] like Figure 1 and Figure 2 As shown, the preparation of Urea-COF in this embodiment includes the following steps:

[0059] The two monomers trialdehyde pyrogallol and 1,1'-(1,4-phenylene) diurea were weighed into an ampoule tube according to a proportion, and solvents NMP, O-DCB and acetic acid solution were added; liquid nitrogen freeze-thaw cycle degassing, the ampoule tube was sealed, and then placed in a 90°C constant temperature oven for reaction for 72 hours; a yellow Urea-COF covalent organic framework material, Urea-COF, was obtained;

[0060] The monomer trialdehyde phloroglucinol is Mmmol, 1,1'-(1,4-phenylene) diurea is Nmmol, the solvent NMP is OmL, O-DCB is PmL, the acetic acid solution is QmL, M:N:O:P:Q=0.1:0.15:0.8:0.2:0.1, such as Figure 2 shown.

[0061] In the method for preparing a flexible solid electrolyte of this embodiment, the concentration of the acetic acid solution is 6 mol / L. Figure 1 The "HOAC (6M, aq.)" in the table refers to a 6 mol / L acetic acid solution.

[0062] Figure 2 Double is the best data, and its structure has higher crystallinity, indicating that the pores are more ordered, which is conducive to battery assembly; all is the comparison group. Figure 2The horizontal axis is the angle. Figure 2 The Chinese meaning of the vertical axis “intensity” is strength.

[0063] Example 2: This example provides a method for preparing a flexible solid electrolyte, which is different from Example 1 in that U:V:X=25:51:10.

[0064] Example 3: Figure 5 and Figure 6 As shown, this embodiment provides a method for preparing a button cell, wherein the active material: binder: conductive agent = 8:1:1 ratio is used for coating, placed in a vacuum oven at 120°C, dried for 6 hours and cut into pieces to obtain LTO / LMO pole pieces, and then the Urea-COF solid electrolyte and pole pieces prepared in Example 1 are assembled in a button cell to obtain a full battery, wherein lithium titanate is used as the negative electrode and lithium manganate is used as the positive electrode.

[0065] In the preparation method of a button battery of this embodiment, the drying temperature of the electrode is selected to be 120° C. and the drying time is 6 hours.

[0066] from Figure 5 It can be seen from the charge and discharge curves that the prepared flexible aqueous solid electrolyte can be charged and discharged normally, meeting the electrical requirements of the LMO / LTO pair. Figure 5 The horizontal axis is time and the vertical axis is voltage. Figure 5 In the figure, charge means charging and discharge means discharging.

[0067] from Figure 6 It can be seen that the cycle performance expresses the stability of the material and proves that the prepared material can meet the battery requirements and complete a stable cycle. Figure 6 In the figure, charge means charging and discharge means discharging.

Claims

1. A method for preparing a flexible solid electrolyte, characterized in that: The following steps are involved: Step 1, activating COF; Step 2, weigh PE and activated COF, grind them evenly, add liquid paraffin and mix them evenly, heat them after mixing, and after PE is completely melted, place the mixture on a roller press to roll it into a flexible porous matrix, soak the flexible porous matrix in dichloromethane, remove the liquid paraffin, and then dry the flexible porous matrix in an oven to obtain a COF flexible porous matrix; Step 3, take the COF flexible porous matrix, weigh the lithium salt and tetrahydrofuran, stir them thoroughly, remove the solvent under vacuum, and obtain a flexible solid electrolyte precursor; Step 4: quantitatively adsorb the hydrophilic substance vapor on the flexible solid electrolyte precursor prepared in step 3 to obtain a COF flexible solid electrolyte; wherein the COF flexible porous matrix is ​​Umg, the lithium salt is Vmg, the hydrophilic substance content is Xmg, and U:V:X=20~30:40~60:5~15.

2. A method for preparing a flexible solid electrolyte according to claim 1, characterized in that: Hydrophilic substances are substances containing hydrogen bonds.

3. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: The hydrophilic substance vapor is water, water vapor, alcohol vapor or ammonia vapor.

4. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: The COF material is a hydrophilic COF.

5. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: The COF material is a COFs structure connected by urea groups.

6. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: The lithium salt is LiTFSI, LiPF6 or LiBOB.

7. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: In step 2, PE is Smg, COF is Rmg, liquid paraffin is Tmg, and R:S:T=9:1:

1.

8. The method for preparing a flexible solid electrolyte according to claim 1, characterized in that: In step 3, the ratio U:V:X=25:51.3:

10.

9. A method for preparing a solid-state battery, characterized in that: Active material: binder: conductive agent =7-9:1-2:1-2 ratio for coating, placed in a vacuum oven at 100-140° C. for drying and cut into pieces to obtain LTO / LMO pole pieces, and then the flexible solid electrolyte and pole piece prepared by any one of claims 1-8 are assembled in a button battery to obtain a full battery.

10. A method for preparing a solid-state battery according to claim 9, characterized in that: The mass ratio of the electrode is active material: binder: conductive agent = 8:1:1.